The allure of stem cell therapy for muscular dystrophy. - Grounds, MD; Davies, K (2007)
Duchenne muscular dystrophy (DMD) is a lethal muscle disease for which an effective treatment is urgently needed. The use of stem cells to produce normal muscle cells to replace the missing dystrophin protein has attracted much attention. Claims of success using stem cell treatment in animal models of human muscle diseases require careful evaluation and are not necessarily easily extrapolated to the clinical situation. Recent studies in the dystrophic dog model have been claimed to show that injected mesangioblasts, stem cells derived from blood vessels, reduce the severity of the disease. However, the authors' interpretation of the results did not consider that benefits might arise from the concomitant use of immunosuppressive drugs alone.